2016
DOI: 10.1175/jamc-d-15-0261.1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the North Atlantic Oscillation on Transatlantic Flight Routes and Clear-Air Turbulence

Abstract: The variation of wind-optimal transatlantic flight routes and their turbulence potential is investigated to understand how upper-level winds and large-scale flow patterns can affect the efficiency and safety of long-haul flights. In this study, the wind-optimal routes (WORs) that minimize the total flight time by considering wind variations are modeled for flights between John F. Kennedy International Airport (JFK) in New York, New York, and Heathrow Airport (LHR) in London, United Kingdom, during two distinct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 28 publications
1
26
0
Order By: Relevance
“…This is one of the reasons for the success in forecasting turbulence of CAT diagnostics containing vertical wind shear [e.g., Colson-Panofsky index (Colson and Panofsky 1965), TI1, TI2 (Ellrod and Knapp 1992)]. Kim et al (2016) studied the impact that the North Atlantic Oscillation (NAO) has on aviation turbulence. The NAO is a measure of the relative strength of the Icelandic low and the Azores high.…”
Section: Clear-air Turbulencementioning
confidence: 99%
See 2 more Smart Citations
“…This is one of the reasons for the success in forecasting turbulence of CAT diagnostics containing vertical wind shear [e.g., Colson-Panofsky index (Colson and Panofsky 1965), TI1, TI2 (Ellrod and Knapp 1992)]. Kim et al (2016) studied the impact that the North Atlantic Oscillation (NAO) has on aviation turbulence. The NAO is a measure of the relative strength of the Icelandic low and the Azores high.…”
Section: Clear-air Turbulencementioning
confidence: 99%
“…This change to the jet stream, therefore, has an impact on turbulence for transAtlantic flights. Kim et al (2016) used wind-optimal routes to find the fastest possible flight path between London (LHR) and New York (JFK). The study found that eastbound flights fly more frequently through regions of CAT than westbound flights, and, therefore, experience more turbulence in both the positive NAO phase and the negative NAO phase.…”
Section: Clear-air Turbulencementioning
confidence: 99%
See 1 more Smart Citation
“…And the turbulence potential along these trajectories also highly depends upon these weather conditions, because local gradients of meteorological variables like horizontal and vertical wind and temperature are generally large within the jet stream (e.g., Kim et al 2016). …”
Section: Long-term Variations Of the Aircraft Trajectories And Turbulmentioning
confidence: 99%
“…Unexpected turbulence encounters at cruising altitudes of z = 8 ~ 12 km are a leading cause of weather hazards for the aviation industry and may cause in‐flight injuries, flight delays, and structural damage [e.g., Sharman et al , ]. Turbulence in the absence of adjacent deep convection is normally referred to as Clear‐Air Turbulence, which often occurs near the upper level jet and frontal system due to shear instability, inertial instability, and geostrophic adjustment or spontaneous imbalance [e.g., Endlich , ; Dutton and Panofsky , ; Shapiro , ; Ellrod and Knapp , ; Knox et al , ; Kim et al , ]. Upper level turbulence can also occur over the complex mountainous regions mainly due to the interactions between mountain waves and the background wind, which is known as mountain‐wave turbulence (MWT) [e.g., Lane et al , ; Kim and Chun , , ; Sharman et al , ].…”
Section: Introductionmentioning
confidence: 99%